1988
DOI: 10.1128/mcb.8.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Expression and biosynthetic variation of the epidermal growth factor receptor in human hepatocellular carcinoma-derived cell lines.

Abstract: Expression of the epidermal growth factor (EGF) was analyzed in six human hepatocellular carcinomaderived and one human hepatoblastoma-derived cell line, each of which retained the differentiated phenotype and functions of the parenchymal hepatocyte. The level of receptor expression of each hepatoma cell line was imilar to that of the normal human fibroblast, approximately 10 molecules per cell. However, NPLC/PRF/5, a subline of the PLC/PRF/5 cell line obtained following reestablishment of a xenograft tumor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
4

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 57 publications
1
26
4
Order By: Relevance
“…These data are at variance with those of others which suggest that either EGF-R expression is decreased in hepatoma cells [27], or that abnormal expression of the EGF-R of HCC-cells is not among the factors responsible for the aberrant cell proliferation [15]. EGF has been observed to inhibit growth in vitro of a variety of carcinoma-derived cell lines [28][29][30][31], most of which exhibit high levels of high-affinity EGF receptors as a consequence of gene amplification.…”
Section: Discusioncontrasting
confidence: 55%
See 1 more Smart Citation
“…These data are at variance with those of others which suggest that either EGF-R expression is decreased in hepatoma cells [27], or that abnormal expression of the EGF-R of HCC-cells is not among the factors responsible for the aberrant cell proliferation [15]. EGF has been observed to inhibit growth in vitro of a variety of carcinoma-derived cell lines [28][29][30][31], most of which exhibit high levels of high-affinity EGF receptors as a consequence of gene amplification.…”
Section: Discusioncontrasting
confidence: 55%
“…A further aspect of HCC cells in culture has been reported concerning their response to polypeptide mitogens [13][14][15], thus indicating that at least in some cases epidermal growth factor (EGF) can play a major role in conditioning the growth characteristics of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of both IGF and IGF receptor is upregulated in HCC and human cirrhotic liver (Alexia et al, 2004) Similarly, EGF and related growth factors are commonly overexpressed in HCC (Yeh et al, 1987;Carlin et al, 1988;Kira et al, 1997;Ito et al, 2001).…”
Section: Pi3k/akt/mtor Signaling Pathwaymentioning
confidence: 99%
“…27À29 The epidermal growth factor receptor (EGFR) is highly expressed in a wide variety of human tumors, such as lung, breast and hepatocellular cancers. 30 The binding of EGF to EGFR triggers the fast internalization of EGF conjugated polyplexes. 31 Our previous studies demonstrated that the EGF-PEG conjugated polyethylenimine (EGF-PEG-PEI) polyplexes delivered pDNA or dsRNA into targeted cells or tumor xenograft much more efficiently than EGF free ones.…”
mentioning
confidence: 99%